Wong Phui Nam: A Critical Biography - Yeoh, Shu Ying (2003)
"Wong Phui Nam: A Critical Biography" is a study of a Chinese Malaysian poet who has produced a significant body of works in the English language. In literature, the biographical approach is well accepted for the study of poets and works of poetry. In fact, it has long been proven effective as a useful and thorough method and is able to provide important and interesting details for a better understanding of a poet and his or her works. Wong Phui Nam has been writing poetry from his base in Kuala Lumpur, Malaysia for almost half a century. A Peranakan by birth but brought up as a Cantonese. Wong was first educated in Chinese and later in English. Wong's poetry, which is c1osely linked to his personal thoughts and experiences, is best studied in the light of his interesting life. He started writing in the mid-fifties, just before the country achieved independence and has not stopped producing poetry through the years. He published his latest book of poetry in 2000. Wong's writings belong to the field of Malaysian literature in English, where there is a lack of supplementary material due to its short history in the country and secondary position where language policies are concerned. As such, this critical biography of Wong Phui Nam would contribute in some manner to this select field. This is because Wong' s four books of poems and various articles on local poetry form an important part of Malaysian literature in English. He has been on the scene of this field since the early stages of the formation of a body of works known as Malaysian literature in English and is one of the few writers from the fifties still producing poetry into the new millennium. Most of the data in this study is obtained from personal interviews and talks given by Wong and his contemporaries. Critical essays by him and articles on him and his works are also studied for a more complete understanding of this man, who is also a poet. This study focuses on how Wong's life has impacted his poetry in a significant and perceptible manner. It shows how he draws inspiration and ideas from his surroundings and how events in his life influence his writings to a great extent. In taking a close look at Wong Phui Nam's life and works, this critical biography helps readers come to a better understanding and a deeper enjoyment of his poetry, which mostly describes a landscape familiar to him and people close to his heart.